Brain ability and its correlation in separation classes for men and women in Islamic educational institutions - Nurul Lubab Abdillah; Wantini Wantini (Edusoshum : Journal of Islamic Education and Social Humanities, 2025)
The purpose of this research is to find a step solution for how to manage classes based on gender while still optimizing the character of the brain. This research method uses a qualitative approach. The results of this research are the differentiation of male and female brains in general in the corpus callosum and Broca-Wernicke's area. This causes women to be more able to carry out several tasks at one time and women are better able to control their emotions. In addition, women also have better language skills, as reflected in the large number of vocabulary products. In Islamic educational institutions, the segregation of classes based on gender is a rule based on religion. In Islam men and women. And it was found that class separation based on gender had the following positive impacts: first, students were more focused. Second, growing awareness that there are boundaries with the opposite sex. Third, increasing learning outcomes.The results of this study have implications for educators to take attitudes and steps in class management by paying attention to existing characters and potential.